Nanoparticles application in high voltage insulation systems - Kadim, Emran Jawad; Ahmad Noorden, Zulkarnain; Adzis, Zuraimy (Institute of Electrical and Electronics Engineers, 2021)
Insulation systems of electrical apparatus (fluid and solid) include transformer oil, insulating paper, glass, ceramic, mica and rubber. Normally, they are designed well to be stable at high temperatures and provide excellent electrical insulating properties in different operating loads. There is an increasing demand to modify the effectiveness and capabilities of these insulation systems to overcome various issues (e.g., overheating, overloading and short circuits). Moreover, they should match the new high voltage insulation requirements, safety, ultra-high voltage, and being environmentally friendly are some of them. Nanoparticles (NPs) are promising compensator materials that can be used to develop insulation systems with good thermophysical and dielectric properties. The results of many studies show marvelous enhancements in electrical and thermal properties. In this paper, the authors present a review that focuses on different NPs that are used in several aspects of insulation systems to improve the dielectric as well as the heat transfer properties of high voltage insulation applications. The review covers NPs types, the preparation methods, analysis approaches, different properties, performances and results, challenges, and the limitation of the use of NPs.